2017
DOI: 10.1002/maco.201709507
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion resistance of austenitic Fe-Mn-C TWIP steel by cerium(III) in 1 M hydrochloric acid pickling solution

Abstract: The influence of rare earth Ce3+ ions on the corrosion behaviour of Fe‐Mn‐C TWIP steel in 1 M hydrochloric acid solution was studied by electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM). Electrochemical corrosion tests showed that Ce3+ can significantly reduce corrosion deterioration up to 1.0 mM. Beyond that level the corrosion rate increases till a steady value. Surface film resistance increases with time evolution until 24 h, then decreases and stabilises. High corrosion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies have shown [19][20][21] that metals treated with cerium present enhanced corrosion resistance. Cerium's outermost electrons are not tightly sealed to the nucleus, and the electronegativity is extremely low; accordingly, a strong attraction exists between Ce and Fe atoms, which increases the bonding force in the rebar and film.…”
mentioning
confidence: 99%
“…Studies have shown [19][20][21] that metals treated with cerium present enhanced corrosion resistance. Cerium's outermost electrons are not tightly sealed to the nucleus, and the electronegativity is extremely low; accordingly, a strong attraction exists between Ce and Fe atoms, which increases the bonding force in the rebar and film.…”
mentioning
confidence: 99%